2003
DOI: 10.1002/dvdy.10255
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Grainyhead‐like epithelial transactivator (GET‐1), a novel mammalian Grainyhead‐like factor

Abstract: LMO-4 is an LIM-only factor that is highly expressed in many epithelial cells, including those of the epidermis and hair follicles. Because LMOs may function by interacting with DNA-binding proteins, we have used the yeast two-hybrid system to screen mouse skin libraries for LMO-4 -interacting DNA-binding proteins. In this screen, we isolated a novel LMO-4 -interacting factor highly related to the Drosophila gene Grainyhead. Grainyhead is epidermally expressed and carries out important functions in cuticular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 81 publications
3
71
0
Order By: Relevance
“…In vertebrates, this family consists of several members, including CRTR-1 (known as LBP-9 in human; Huang and Miller, 2000), CP2 (also known as LBP-1c and LSF; Lim et al, 1992;Shirra et al, 1994), NF2d9 (known as LBP-1a in human; Sueyoshi et al, 1995;Yoon et al, 1994), mammalian Grainyhead (MGR), brother of MGR (BOM; Wilanowski et al, 2002), sister of MGR (SOM)/GET1 (Kudryavtseva et al, 2003;Ting et al, 2003b), but their developmental roles have been largely unknown (Ramamurthy, 2001;Ting et al, 2003a). We found that CRTR-1 was specifically expressed in the ductal epithelium of the kidney and the salivary glands (Fig.…”
Section: Roles Of the Trapped Genes In Clone 43 And Clone 5 During Momentioning
confidence: 99%
“…In vertebrates, this family consists of several members, including CRTR-1 (known as LBP-9 in human; Huang and Miller, 2000), CP2 (also known as LBP-1c and LSF; Lim et al, 1992;Shirra et al, 1994), NF2d9 (known as LBP-1a in human; Sueyoshi et al, 1995;Yoon et al, 1994), mammalian Grainyhead (MGR), brother of MGR (BOM; Wilanowski et al, 2002), sister of MGR (SOM)/GET1 (Kudryavtseva et al, 2003;Ting et al, 2003b), but their developmental roles have been largely unknown (Ramamurthy, 2001;Ting et al, 2003a). We found that CRTR-1 was specifically expressed in the ductal epithelium of the kidney and the salivary glands (Fig.…”
Section: Roles Of the Trapped Genes In Clone 43 And Clone 5 During Momentioning
confidence: 99%
“…We and others have found that LMO4 can interact with distinct DNA-binding proteins expressed at these locations (Sugihara et al, 1998;Sum et al, 2002;Kudryavtseva et al, 2003;Manetopoulos et al, 2003). As LMO4 is highly expressed at multiple sites of mesenchymal-epithelial interactions, it is attractive to propose that LMO4 interacts with and modulates the function of DNA-binding proteins in conserved signaling pathways involved in mesenchymal-epithelial signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Several LMO4-interacting proteins have been identified, including the ubiquitous nuclear adaptor protein Lbd1 (Grutz et al, 1998), the transcription factor deformed epidermal autoregulatory factor 1 (Sugihara et al, 1998), the basic helix-loop-helix protein HEN1 (Manetopoulos et al, 2003) and the grainyhead-like epithelial transactivator (Kudryavtseva et al, 2003), as well as the cofactor CtIP and BRCA1.…”
Section: Discussionmentioning
confidence: 99%